Language and culture. The features of character of the Ukrainians as a component of the national culture (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article deals with the questions devoted to the definitions of «language», «culture», «the language picture of the world» and «the features of the national character». Any language reflects national culture, and this fact helps to understand the language picture of the world better. Language and culture are interdependent.  It is commonly used fact that cultural processes influence on language, and vice versa. One of the indicators of the national culture is mentality, features of human character.
Keywords: the language picture of the world; language; culture; national character; features of character